Keragaan Agronomis dan Kelayakan Usahatani Kedelai yang Dibudidayakan Secara Monokultur dan Polikultur di Sumatera Selatan - Renny Utami Somantri; Syahri Syahri; Tumarlan Thamrin (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2019)
Somantri RU, Syahri S, Thamrin T. 2019. Agronomic and economic analysis of soybeans which is grew by monoculture and polyculture systems in South Sumatra. Jurnal Lahan Suboptimal: Journal of Suboptimal Lands. 8(2):159-172. The presence of shade and other limiting factors in the crops of plantation plants will certainly affect the growth and soybean yield were compared by monoculture. The objective of the research was to know of agronomic performance and farming feasibility of soybeans which are cultivated by polyculture and monoculture systems. Soybeans were planted in two systems namely monoculture (soybean) and polyculture (soybean are intercropped with 3 years of rubber trees). Both of Dena 1 and Anjasmoro varieties were cropped in those systems. Soybeans are cropped by using planting machine (ATBJ) which has planting distance 20 cm x 40 cm (1-2 seeds per hole). Plants were fertilized with 50 kg Urea per ha, 150 kg TSP per ha, 150 kg KCl per ha, manure 2,000 kg per ha, and dolomite 1,000 kg per ha. Mower were used for harvesting. The results showed that the growth and soybean yield in monoculture system was better than the polyculture. Yield of Anjasmoro in monoculture was 15.35 ku per ha, whereas the polyculture was 4.72 ku per ha. Meanwhile, the productivity of Dena 1 was 14.80 ku per ha and 7.38 ku per ha in polyculture system. The polyculture had a higher value of the land equivalent ratio than monoculture of rubber trees. Economically, the two planting systems that were examined also deserve to be done by farmers, where the value R/C > 1